2016
DOI: 10.1111/vop.12370
|View full text |Cite
|
Sign up to set email alerts
|

Sudden acquired retinal degeneration in dogs: breed distribution of 495 canines

Abstract: As previously reported, SARD is most common in middle-aged to older dogs. Smaller dogs of less than 25 pounds appear overrepresented, while large/giant breed dogs of greater than 50 pounds are infrequently diagnosed. In this study, there was no statistical significance between female and male dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 8 publications
7
16
0
3
Order By: Relevance
“…1 SARDS is most frequently seen in middle aged/older females of small breeds, with mixed-breed dogs, Dachshunds, Pugs, and Miniature Schnauzers being the most frequently affected, which corresponds to our findings in this study. 2,3,24,25 Previous studies found a relatively high incidence of metabolic abnormalities, such as polyuria and polydipsia (38%, 2 30% 3 ), polyphagia (19%, 2 20% 3 ), and alkaline phosphatase elevation (37%, 2 28% 3 ), which was also in good accord with our findings in similar percentages. The most recent study of a Canadian patient population, however, revealed much higher incidence of metabolic abnormalities in SARDS patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1 SARDS is most frequently seen in middle aged/older females of small breeds, with mixed-breed dogs, Dachshunds, Pugs, and Miniature Schnauzers being the most frequently affected, which corresponds to our findings in this study. 2,3,24,25 Previous studies found a relatively high incidence of metabolic abnormalities, such as polyuria and polydipsia (38%, 2 30% 3 ), polyphagia (19%, 2 20% 3 ), and alkaline phosphatase elevation (37%, 2 28% 3 ), which was also in good accord with our findings in similar percentages. The most recent study of a Canadian patient population, however, revealed much higher incidence of metabolic abnormalities in SARDS patients.…”
Section: Discussionsupporting
confidence: 92%
“…Sudden Acquired Retinal Degeneration Syndrome was first reported almost four decades ago; however, the precise etiology of the disease is still being extensively debated without a clear consensus on its exact nature . SARDS is most frequently seen in middle aged/older females of small breeds, with mixed‐breed dogs, Dachshunds, Pugs, and Miniature Schnauzers being the most frequently affected, which corresponds to our findings in this study . Previous studies found a relatively high incidence of metabolic abnormalities, such as polyuria and polydipsia (38%, 30%), polyphagia (19%, 20%), and alkaline phosphatase elevation (37%, 28%), which was also in good accord with our findings in similar percentages.…”
Section: Discussionsupporting
confidence: 86%
“…SARDS typically affects middle‐aged to elderly and often moderately overweight dogs . The reported mean or median ages of affected dogs range from 7 to 10 years .…”
Section: What Is Sards?mentioning
confidence: 99%
“…SARDS typically affects middle‐aged to elderly and often moderately overweight dogs . The reported mean or median ages of affected dogs range from 7 to 10 years . Between 60 and 90% of affected dogs are female; the majority of them are spayed .…”
Section: What Is Sards?mentioning
confidence: 99%
See 1 more Smart Citation